APPLICATION OF LANGUAGE GAME LEARNING MODEL TO IMPROVE ENGLISH COMMUNICATION SKILLS OF CLASS IX C STUDENTS AT UPT SMPN 25 GRESIK ACADEMIC YEAR 2021/2022 - Nur Azizah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Academic anxiety about the low communication skills of high school students prompted researchers to develop a learning model emphasizing oral communication practices as the main target in classroom teaching-learning. The learning model developed emphasizes the objectives of learning English in secondary schools (SMP/MTs), which are oral communication skills and adaptation to the level of student development. The author is interested in conducting research with the title: “Application of Language Game Learning Models to Improve English Communication Skills of Class IX C at UPT SMPN 25 Gresik Academic Year 2021/2022”. Language games are important to create active, innovative, creative, effective, and fun learning by emphasizing the main orientation of English learning in Junior High School (SMP/MTs), particularly oral communication skills.The author is interested in conducting research with the title: “Application of Language Game Learning Models to Improve English Communication Skills of Class IX C at UPT SMPN 25 Gresik Academic Year 2021/2022”.The Application of the Language Game Learning Model (Contextual Teaching and Learning) can improve the social studies achievement of Class IX C students of UPT SMPN 25 Gresik academic year 2021/2022. The average score acquisition of student learning is: 1) from the pre test results it is concluded that the average acquisition of student learning outcomes before action is 58 with a percentage of KKM completeness which is 27 %, 2) student learning outcomes in the second cycle, the average student acquisition increased to 78.3 with a percentage of completeness KKM 100